PENERAPAN SISTEM MANAJEMEN RISIKO PADA PT PERUSAHAAN PELAYARAN NUSANTARA PANURJWAN - Fadhlih Rizky Sawa Madani (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This journal was created because it remembers the awareness of the importance of implementing K3 in the workplace, especially at ports. Implementing K3 is something that must be done by everyone involved in work in this scope in order to create a safe and comfortable work environment. This study aims to find out how the application of K3 and risk control at PT Perusahaan Pelayaran Nusantara Panurjwan. The research method used is quantitative with primary and secondary data attached.